A Fatal Case of Influenza B Myocarditis with Cardiac Tamponade. (30th August 2018) - Roto, Dominick; Malnoske, Michelle L.; Winters, Shira; Georas, Steve N.
Abstract : Background . Influenza B is generally regarded as a less severe counterpart to influenza A, typically causing mild upper respiratory symptoms. Myocardial involvement with influenza B is a rare complication, better described in children than adults. However, when it occurs, it can lead to profound myocarditis with progression to shock requiring aggressive supportive care. Case Presentation . We present a case of cardiac tamponade in the setting of influenza B infection in a previously healthy 57-year-old woman, with progression to refractory shock and death. Autopsy revealed myocardial necrosis with infiltration of CD3+ lymphocytes, and little evidence of viral pneumonia. Conclusions . Myocarditis is a rare complication of influenza B in adults, and subsequent pericardial effusion with tamponade physiology is a previously unreported event in an otherwise healthy adult without other medical comorbidities. While rare, this is a serious and potentially fatal complication that clinicians should be aware of when evaluating a patient with suspected viral illness who is exhibiting shock physiology.